Antara Validitas Keagamaan dan Pengakuan Administratif: Penetapan Nasab Anak dalam Hukum Keluarga Islam di Indonesia - Jaya Pirgo; Widiya Yul (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
The determination of child lineage in Indonesia reflects the interaction between Islamic law and state law within a plural legal system. Legal uncertainty often arises when marriages are religiously valid but administratively unregistered, affecting the civil status and rights of children. This article examines judicial reasoning in Decision No. 229/Pdt.P/2025/PA.Spn of the Sungai Penuh Religious Court concerning the determination of a child’s lineage. Using normative legal research with a doctrinal case-study approach, the study analyzes statutory regulations, Islamic legal principles, and the court’s ratio decidendi. The findings show that the court integrates the substantive validity of marriage under Islamic law with national legal principles on child protection and civil status. The article proposes a reconstructive framework for determining child lineage based on three elements: substantive marital validity, layered evidentiary standards, and institutional coordination between religious courts and civil registration authorities